Integrated Transportation, Building, and Electricity System Models to Explore Decarbonization Pathways in Regina, Saskatchewan - Seatle, Madeleine; Stanislaw, Lauren; Xu, Robert; McPherson, Madeleine (Frontiers in Sustainable Cities, 2021)
In Canada, the majority of urban energy demand services the transportation or building sectors, primarily with non-renewable energy sources including gasoline and natural gas. As a result, these two sectors account for 70% of urban greenhouse gas (GHG) emissions. Electrification policies including electric vehicle adoption, building retrofits, and increased generation of low-carbon electricity offer significant decarbonization potential. This paper focuses on Regina, Saskatchewan, which aims to be powered with 100% renewable energy by 2050 and is in a region rich with solar and wind resources. This paper explores the potential for co-benefits when simultaneously electrifying transportation and building demand sectors while expanding variable renewable energy (VRE) production. The investigation uses a novel integrated framework of the transportation, building, and electricity sectors to represent the operational implications of demand side flexibility on both the demand and supply side of the energy system. First, the activity-based transportation model produces passenger travel demand profiles, allowing for investigation of potential electricity demand and demand response from electric vehicles with high spatial and temporal resolution. Second, the archetype-based building model predicts electricity demand of the residential building sector, allowing for investigation into demand-side management strategies such as load-shifting, building retrofits, and changes in appliance technology. Third, the electricity system production cost dispatch model is used to model the operations of Regina’s electricity grid and has a spatial resolution capable of assessing individual and connected positive energy districts as well as VRE integration. These three models are linked through bidirectional flow of model inputs and outputs. Through linking of these three models, the effects of consumer flexibility in transportation and building energy demand are explored, especially in the context of introducing much needed flexibility for large-scale VRE integration. A utility-controlled demand response (DR) strategy is explored as means for Regina to reach their renewable target, along with battery storage. The results show that Regina can meet their renewable target with large-scale rooftop solar and wind capacity. Battery storage is essential when considering pathways to meet the target, while utility-controlled residential DR has very little effect on the increased integration of renewables into the generation mix.